Hubungan antara Lamanya Aktivitas Melihat Dekat dengan Miopia pada Anak di SDN Cemara 2 Surakarta - Purbaningrum, Eli Dwy; Indrakila, Senyum; Primadewi, Novi (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: The most common type of refractive error in school student was myopia. Some factors are predicted play a role in the onset of myopia, one of them is nearwork activity. Meanwhile, the globalization encourages children to do some nearwork activities, such as reading and using gadgets. The purpose of this study was to analyze the the relationship between duration of nearwork activity and children myopia. Methods: This study used observational analytic method with cross-sectional design research. The population was all students of SDN Cemara 2 Surakarta. Subjects were students of grade III to V who are either suffering myopia or not. The total subject were 200 children, which was 100 children with myopia picked by fixed disease sampling technique, and 100 children with no myopia picked by simple random sampling technique. The data were collected by measurement with autorefractometre and questionnaires. The data obtained were analyzed by using multiple logistic regression with SPSS 17.0 for Windows. Result: From 200 subjects found that total children myopia who do nearwork activities longer 54 (52%) and children with no myopia who do nearwork activities longer 50 (48%). The results of multiple logistic regression statistical test showed that duration of nearwork activity and children myopia have no significant relationship statistically (p = 0,59). Conclusion: There was no significant relationship between duration of nearwork activity and children myopia.Â